Long‐term efficacy of rituximab in IgM anti‐myelin‐associated glycoprotein neuropathy: RIMAG follow‐up study. Issue 1 (March 2016) - Iancu Ferfoglia, Ruxandra; Guimarães‐Costa, Raquel; Viala, Karine; Musset, Lucile; Neil, Jean; Marin, Benoit; Léger, Jean‐Marc
Abstract: The Rituximab vs. Placebo in Polyneuropathy Associated With Anti‐MAG IgM Monoclonal Gammopathy (RIMAG) study showed no improvement using the inflammatory neuropathy cause and treatment sensory score (ISS) as primary outcome in patients with IgM anti‐myelin‐associated glycoprotein neuropathy (IgM anti‐MAG neuropathy) treated with rituximab, when compared with placebo. However, some secondary outcomes seemed to improve in the per protocol analysis. Patients from one participating center in the RIMAG study underwent a new evaluation after a median follow‐up of 6 (interquartile range (IQR) 4.9; 6.5) years, using the same outcome measures used in the original study. Data were recorded in seven rituximab patients (group 1) and in eight placebo patients (group 2). In group 2, six of eight patients received immunotherapy during follow‐up, while only two of seven did in group 1. No significant change was observed in either the ISS or the secondary outcomes in both groups, with the exception of worsening in the 10‐m walk time in group 2 ( p = 0.016). The RIMAG follow‐up study failed to find any significant change in most outcome measures in patients from the RIMAG study, some of them having received new immunotherapies. This study stresses the lack of useful clinical scales sensitive enough to capture small, even meaningful, improvement in IgM anti‐MAG neuropathy.